The Effect of Money Supply, Exchange Rate, and Interest Spread toward the Performance of Stock Market in Malaysia - Yeoh Kai Qing; Suhal Kusairi (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2019)
The stock market has become a significant role in the economy and has attracted investor's attention, as it is to generate funds and make an investment decision for companies and investors as well. Therefore, the objective of this study is to study the effect of the money supply, exchange rate, interest spread and stock market in the short and long run and volatility issue. The study employed monthly data, from January 1997 to August 2018. Method analysis is the Autoregressive distributed lag (ARDL) and GARCH model. The findings stated that the money supply, real effective exchange rate, interest spread, had a long-run effect on the performance of the stock market. Money supply and the real effective exchange rate had a positive effect on the stock market performance in the short run. Conversely, the interest spread showed a negative influent on the stock market performance in the short run. The volatility indicated a high persistence between the money supply, real effective exchange rate, interest spread and stock market (KLCI). The implication of the study is the investors or policymakers should take account the changes of interest rate and exchange rate before making stock investment or policy to stabilize the stock market performance.